PROSPECTS OF SYNTHETIC POLYMERS APPLICATION AS INERT CARRIERS FOR β-GALACTOSIDASE IMMOBILISATION - Victoria Evgen'evna Suprunchuk; Aleksei Dmitrievich Lodygin; Evgeniya Vladimirovna Denisova (Наука. Инновации. Технологии, 2022)
The actuality of lactose-reduced and delactosed products manufacturing is founded. Methods of β-galactosidase immobilization and it’s peculiarities, concerned with type of carrier, are considered. Ways of covalent link formation for lactose binding by synthetic polymers are presented.